The Kamar - Dube, S. C. (Shyama Charan), 1922-1996. (New Delhi ; Oxford : Oxford University Press, 2012)
This title is an important ethnography of an exploited and marginalised tribe in transition. It is a pioneering portrait of the Kamar, an Adivasi community of hunter-gatherers and shifting-cultivators of Chattisgarh and Orissa.
Previous ed.: 2004.
Description based on online resource; title from PDF title page (viewed on Sept. 4, 2012).
Includes bibliographical references and index.
Keywords: Kamar (Indic people) -- History; Kamar (Indic people) -- Social life and customs